Fecal microbiota transplantation as salvage therapy for disseminated strongyloidiasis in an immunosuppressed patient: a case report - Fu, Wei; Peng, Na; Geng, Yan (Frontiers in Immunology, 2025)
BackgroundDisseminated strongyloidiasis carries high mortality in immunosuppressed populations. We report a case of refractory Strongyloides stercoralis-induced severe diarrhea and sepsis successfully treated with fecal microbiota transplantation (FMT).Case presentationA 68-year-old male with nephrotic syndrome on long-term glucocorticoids developed hyperinfection syndrome manifesting as septic shock, multiorgan dysfunction, and intractable diarrhea (>30 episodes/day). Conventional therapies including antiparasitics (albendazole), antibiotics, and probiotics failed. FMT achieved rapid symptom resolution and microbiota restoration.ConclusionThis case highlights FMT’s potential in modulating gut-parasite interactions and suggests its role as adjunctive therapy for parasitic hyperinfection syndromes.